Method for preparing electrode active material
By preparing Li1+xTM1-xO2 electrode active material, the combination of nickel, cobalt and manganese and the oxides of lithium, Al, Ti or W are heat treated at high temperatures, the problems of cycle stability and capacity loss of the positive electrode material of lithium-ion batteries are solved. , achieving higher cycle stability and capacity retention.
Patent Information
- Application Number
- CN201880041849.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2017-07-14
- Filing Date
- 2018-07-05
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2039-09-04
AI Technical Summary
The positive electrode materials of existing lithium-ion battery packs are prone to stability problems and capacity losses during the cycle, especially due to the instability caused by the existence of Li2CO3.
A method for preparing Li1+xTM1-xO2 electrode active material, wherein TM is a combination of nickel, cobalt and manganese, at least 60 mol% is nickel by mixing oxides of Mn, Co and Ni, lithium compounds and The oxide of Al, Ti or W is heat treated at a temperature of 700-1000°C.
This method can significantly improve the cycle stability and capacity maintenance of electrode active materials, reduce the generation of Li2CO3, and thus extend the life of lithium-ion batteries.
Abstract
Description
[0001] The present invention relates to a method for preparing a general formula Li 1+x TM 1-x A method for producing an electrode active material for O2, wherein TM is a combination of Mn, Co and Ni in combination with at least one metal M selected from Al, Ti and W, wherein at least 60 mol% of TM is Ni, the percentage being relative to the sum of Ni, Co and Mn, and x is 0-0.2, the method comprising the following steps:
[0002] (a) Mix the following ingredients:
[0003] (A) a mixed oxide or oxyhydroxide of Mn, Co and Ni, and
[0004] (B) at least one lithium compound selected from lithium hydroxide, lithium oxide and lithium carbonate, and
[0005] (C) oxides, hydroxides or oxyhydroxides of Al, Ti or W,
[0006] (b) heat treating the mixture at a temperature of 700-1000°C.
[0007] Lithiated transition metal oxides are currently used as electrode active materials for lithium-ion batteries. Over the past few years, extensive research and development efforts have been conducted to improve properties such as charge density, specific energy, and other properties such as reduced cycle life and capacity loss, which may adversely affect the life or suitability of lithium-ion batteries. Other efforts have been made to improve the preparation methods.
[0008] Many of the electrode active materials currently discussed are of the lithiated nickel cobalt manganese oxide type ("NCM materials").
[0009] In a typical method for preparing positive electrode materials for lithium-ion batteries, a so-called precursor is first formed by coprecipitating a transition metal in the form of a carbonate, an oxide or preferably a hydroxide (which may be alkaline or non-alkaline). The precursor is then mixed with a lithium salt (for example, but not limited to LiOH, Li2O or especially Li2CO3) and calcined (roasted) at a high temperature. The lithium salt can be used in a hydrate or dehydrated form. Calcination or roasting (also commonly referred to as heat treatment or heat treatment of the precursor) is generally carried out at a temperature of 600-1,000°C. During the heat treatment, a solid-state reaction occurs and an electrode active material is formed. In the case of using hydroxides or carbonates as precursors, the solid-state reaction is carried out after removing water or carbon dioxide. The heat treatment is carried out in the heating zone of an oven or a kiln.
[0010] Dopants in NCM materials, such as aluminum, titanium or tungsten, can positively affect the stability of the NCM material in terms of cycling stability and area resistivity. Li2CO3 derived from unreacted lithium carbonate as the starting material or Li2CO3 formed by absorption of carbon dioxide by alkaline electrode active materials may impair this stability.
[0011] Therefore, the object of the present invention is to provide a method for preparing an electrode active material having high cycle stability. In particular, the object of the present invention is to provide a method for preparing an electrode active material having a low Li2CO3 content.
[0012] Thus, the process defined at the outset has been found, hereinafter also defined as process of the invention or process according to the invention. The process of the invention will be described in more detail hereinafter.
[0013] The method of the present invention is to prepare the general formula Li 1+x TM 1-x A method for producing an electrode active material for O2, wherein TM is a combination of Mn, Co and Ni in combination with at least one metal M selected from Al, Ti and W, wherein at least 60 mol% of TM is Ni, the percentage being relative to the sum of Ni, Co and Mn, and x is 0-0.2, preferably 0.01-0.05, the method comprising the following steps, hereinafter also referred to as step (a) and step (b), respectively.
[0014] Step (a) comprises mixing the following components:
[0015] (A) a mixed oxide or oxyhydroxide of Mn, Co and Ni, hereinafter also referred to as oxyhydroxide (A) or oxide (A), respectively, or collectively referred to as precursor (A), and
[0016] (B) at least one lithium compound selected from lithium hydroxide, lithium oxide and lithium carbonate, hereinafter also referred to as lithium salt (B) or lithium compound (B), and
[0017] (C) An oxide, hydroxide or oxyhydroxide of Al, Ti or W, hereinafter also referred to as compound (C), wherein at least 60 mol % of TM is Ni, relative to the sum of Ni, Co and Mn.
[0018] In one embodiment of the present invention, the precursor (A) is obtained by coprecipitation of mixed hydroxides of nickel, cobalt and manganese, followed by drying and partial or complete dehydration in air.
[0019] The precursor (A) can be obtained by coprecipitating nickel, cobalt and manganese in the form of hydroxides, followed by drying in an oxygen-containing atmosphere and subjecting the mixture to a thermal pretreatment in an oxygen-containing atmosphere.
[0020] The precursor (A) is preferably obtained by coprecipitating nickel, cobalt and manganese in the form of hydroxides from an aqueous solution containing nitrates, acetates or preferably sulfates of nickel, cobalt and manganese in a stoichiometric ratio corresponding to TM. The coprecipitation is carried out by adding an alkali metal hydroxide, such as potassium hydroxide or sodium hydroxide, in a continuous, semi-continuous or batch process. Then, after the coprecipitation, the mother liquor is taken out, for example filtered, and the water is then removed.
[0021] Even more preferably, the TM in the target electrode active material is identical to the TM plus metal M in the precursor (A), see below.
[0022] The removal of water is preferably carried out in at least two sub-steps at different temperatures, for example 80-150° C. in sub-step 1 and 165-600° C. in sub-step 2.
[0023] In one embodiment of the present invention, the removal of water is carried out in different devices. Sub-step 1 is preferably carried out in a spray dryer, a rotary flash dryer or a contact dryer. Sub-step 2 can be carried out in a rotary kiln, a roller bottom kiln or a box kiln.
[0024] The precursor (A) is in the form of particles. In one embodiment of the present invention, the average particle size (D50) of the precursor (A) is 6-12 μm, preferably 7-10 μm. In the context of the present invention, the average particle size (D50) refers to the median value of the volume-based particle size, which can be determined, for example, by light scattering.
[0025] The secondary particles of the precursor (A) are preferably spherical, i.e. particles having a spherical shape. Spherical particles should include not only those that are perfect spheres but also those whose maximum and minimum diameters of at least 90% (number average) of typical samples differ by no more than 10%.
[0026] In one embodiment of the present invention, the precursor (A) consists of secondary particles that are agglomerates of primary particles. Preferably, the precursor (A) consists of spherical secondary particles that are agglomerates of primary particles. Even more preferably, the precursor (A) consists of spherical secondary particles that are agglomerates of spherical primary particles or flakes.
[0027] In one embodiment of the present invention, the particle size distribution range of the precursor (A) may be 0.5-0.9, which range is defined as [(D90)-(D10)] divided by (D50), all determined by laser analysis. In another embodiment of the present invention, the particle size distribution range of the precursor (A) may be 1.1-1.8.
[0028] In one embodiment of the present invention, the surface area (BET) of the precursor (A) is 2-10 m 2 / g, determined by nitrogen adsorption, for example in accordance with DIN-ISO 9277:2003-05.
[0029] In one embodiment of the invention, the precursor (A) may have a uniform distribution of the transition metals nickel, cobalt and manganese over the particle diameter. In other embodiments of the invention, the distribution of at least two of nickel, cobalt and manganese is non-uniform, for example showing a gradient of nickel and manganese, or showing layers of at least two of nickel, cobalt and manganese at different concentrations. Preferably, the precursor (A) has a uniform distribution of the transition metals over the particle diameter.
[0030] In one embodiment of the invention, the precursor (A) may contain elements other than nickel, cobalt and manganese, such as titanium, aluminum, zirconium, vanadium, tungsten, molybdenum, niobium or magnesium, for example in an amount of 0.1-5 mol% relative to TM. However, it is preferred that the precursor (A) contains only negligible amounts of elements other than nickel, cobalt and manganese, for example at most a detection level of 0.05 mol%.
[0031] Precursor (A) may contain trace amounts of metal ions, such as trace amounts of ubiquitous metals such as sodium, calcium, iron or zinc as impurities, however these trace amounts will not be considered in the description of the present invention. In this context, trace amounts mean an amount of 0.05 mol% or less relative to the total metal content of TM.
[0032] In one embodiment of the present invention, when the precursor (A) is prepared by coprecipitation from a solution of one or more sulfates of nickel, cobalt and manganese, the precursor (A) contains one or more impurities, such as residual sulfate. The sulfate may be 0.1-0.4 wt % relative to the total precursor (A).
[0033] In one embodiment of the present invention, TM has the general formula (I):
[0034] (Ni a Co b Mn c ) 1-d M d (I)
[0035] in:
[0036] a is 0.6-0.85, preferably 0.6-0.7,
[0037] b is 0.05-0.2, preferably 0.1-0.2,
[0038] c is 0.05-0.2, preferably 0.1-0.2, and
[0039] d is 0.005-0.1,
[0040] M is Al, and
[0041] a+b+c=1.
[0042] In a preferred embodiment of the invention, at least 60 mol%, e.g. 60-95 mol%, more preferably 60-90 mol%, even more preferably 60-80 mol% of TM is Ni, wherein the percentages are in each case relative to the sum of Ni, Co and Mn. A specific example is Ni 0.5 Co 0.2 Mn 0.3 、Ni 0.6 Co 0.2 Mn 0.2 、Ni 0.8 Co 0.1 Mn 0.1 and Ni 0.7 Co 0.2 Mn 0.1 .
[0043] In one embodiment of the present invention, the precursor (A) is an oxide or oxyhydroxide of TM, and the resulting electrode active material is Li 1+x TM 1-x O2, wherein TM in the precursor (A) is identical in amount of transition metal to the metal in the electrode active material minus M selected from Al, Ti and W, as the case may be.
[0044] As precursor (A), oxyhydroxides with a residual moisture content of 0.1 to 50 wt.-% are particularly feasible. In the context of precursor (A), the moisture content is calculated as g H2O / 100 g of precursor (A). In this case, the H2O can be chemically bound as hydroxyl groups or by physical adsorption. Preferably, the residual moisture in the precursor (A) is low, for example 0.1 to 5 wt.-%. Even more preferably, the precursor (A) is a TM oxide without detectable amounts of residual moisture.
[0045] Examples of lithium compounds (B) are Li2O, LiOH and Li2CO3, if appropriate in each case anhydrous or in the form of a hydrate, for example LiOH.H2O. A preferred example is lithium hydroxide.
[0046] The lithium compound (B) is preferably in the form of particles, for example having an average diameter (D50) of 3-10 μm, preferably 5-9 μm.
[0047] Compound (C) can be used as a dopant source. Compound (C) is selected from the oxides, hydroxides and oxyhydroxides of Ti, W and in particular Al. Lithium titanate is also a possible source of titanium. Examples of compound (C) are WO3, TiO2 selected from rutile and anatase, preferably anatase, and also basic titanium dioxide, such as TiO(OH)2, and also Li4Ti5O 12 , WO3, Al(OH)3, Al2O3, Al2O3·water and AlOOH. Preferred are Al compounds such as Al(OH)3, α-Al2O3, γ-Al2O3, Al2O3·water and AlOOH. Even more preferred compound (C) is Al2O3 selected from α-Al2O3, γ-Al2O3, most preferably γ-Al2O3.
[0048] In one embodiment of the present invention, the surface area (BET) of compound (C) may be 1-200 m 2 / g, preferably 50-150m 2 / g. The BET surface area can be determined by nitrogen adsorption, for example in accordance with DIN-ISO 9277:2003-05.
[0049] In one embodiment of the present invention, compound (C) is a nanocrystal. Preferably, the average crystallite diameter of compound (C) is at most 100 nm, preferably at most 50 nm, even more preferably at most 15 nm. The minimum diameter may be 4 nm.
[0050] In one embodiment of the present invention, compound (C) is a particulate material having an average diameter (D50) of 1-10 μm, preferably 2-4 μm. Compound (C) is usually in the form of agglomerates. Its particle size refers to the diameter of the agglomerates.
[0051] In a preferred embodiment, compound (C) is used in an amount of up to 1.5 mol% (relative to the sum of Ni, Co and Mn), preferably 0.1-0.5 mol%.
[0052] Examples of suitable apparatus for carrying out step (a) are high shear mixers, tumble mixers, plow blade mixers and free fall mixers.
[0053] In one embodiment of the present invention, step (a) is carried out at a temperature ranging from ambient temperature to 200°C, preferably 20-50°C.
[0054] In one embodiment of the invention, the duration of step (a) is from 10 minutes to 2 hours.Depending on whether additional mixing is performed in step (b), thorough mixing must be achieved in step (a).
[0055] The mixing of the precursor (A), the lithium compound (B) and the compound (C) can be carried out in one step or in multiple sub-steps, for example by first mixing the lithium compound (B) and the compound (C) and adding the mixture to the precursor (A); or by first mixing the precursor (A) and the lithium compound (B) and then adding the compound (C); or by first mixing the compound (C) and the precursor (A) and then adding the lithium compound (B). Preferably, the precursor (A) and the lithium compound (B) are first mixed and then the compound (C) is added.
[0056] Although an organic solvent, such as glycerol or ethylene glycol or water may be added in step (a), it is preferred to carry out step (a) in a dry state, ie without adding water or an organic solvent.
[0057] A mixture was obtained.
[0058] Step (b) comprises heat treating the mixture at a temperature of 700-1000°C, preferably 750-925°C.
[0059] In one embodiment of the present invention, the mixture of the precursor (A) and the lithium compound (B) with the residual (C) and optionally one or more solvents is heated to 700-1000° C., wherein the heating rate is 0.1-10° C. / min.
[0060] In one embodiment of the present invention, the temperature is increased and then reaches the desired temperature of 700-1000° C., preferably 750-900° C. For example, the mixture of precursor (A) and lithium compound (B) and compound (C) is first heated to a temperature of 350-550° C., then kept constant for a period of 10 minutes to 4 hours, and then increased to 700-1000° C.
[0061] In embodiments where at least one solvent is used in step (a), the solvent is removed as part of step (b) or separately and before step (b) begins, for example by filtering, evaporating or distilling the solvent. Preferred are evaporation and distillation.
[0062] In one embodiment of the invention, step (b) is carried out in a roller hearth kiln, a pusher kiln or a rotary kiln or a combination of at least two of the foregoing. A rotary kiln has the advantage that the material produced therein is very well homogenized. In roller hearth kilns and pusher kilns, different reaction conditions can be set very easily for the different steps. In laboratory-scale experiments, box furnaces and tube furnaces as well as split tube furnaces are also feasible.
[0063] In one embodiment of the invention, step (b) is carried out in an oxygen-containing atmosphere, for example, in a nitrogen-air mixture, in a noble gas-oxygen mixture, in air, in oxygen or in oxygen-enriched air. In a preferred embodiment, the atmosphere in step (b) is selected from air, oxygen and oxygen-enriched air. Oxygen-enriched air can be, for example, a 50:50 volume ratio mixture of air and oxygen. Other options are a 1:2 volume ratio mixture of air and oxygen, a 1:3 volume ratio mixture of air and oxygen, a 2:1 volume ratio mixture of air and oxygen, and a 3:1 volume ratio mixture of air and oxygen.
[0064] In one embodiment of the present invention, step (b) of the present invention is carried out under a gas stream such as air, oxygen and oxygen-enriched air. This gas stream can be referred to as a forced gas stream. 1+x TM 1-x O2, the airflow can have a range of 0.5-15m 3 / h·kg material specific flow rate. The volume is determined under standard conditions: 298 Kelvin and 1 atmosphere. The gas stream can be used to remove gaseous cracking products, such as water and carbon dioxide.
[0065] The method of the present invention may include further steps, such as, but not limited to, an additional calcination step at a temperature of 500-1000° C. after step (b).
[0066] In one embodiment of the present invention, the duration of step (b) is 1-30 hours. Preferably, it is 10-24 hours. In this context, the cooling time can be ignored.
[0067] After the heat treatment according to step (b), the electrode active material thus obtained is cooled and then further processed.
[0068] By implementing the method of the present invention, an electrode active material having excellent properties can be obtained by a direct method. Preferably, the electrode active material thus obtained has a molecular weight of 0.1 to 0.8 m / s measured according to DIN-ISO 9277: 2003-05. 2 / g surface area (BET).
[0069] In one embodiment of the present invention, it can be detected that in particular Al is uniformly distributed in the electrode active material obtained according to the process of the present invention without accumulation.
[0070] The invention is further illustrated by working examples.
[0071] Embodiment 1:
[0072] A stirred tank reactor was charged with deionized water and 49 g ammonium sulfate / kg water. The solution was tempered to 55°C and the pH was adjusted to 12 by adding aqueous sodium hydroxide solution.
[0073] The coprecipitation reaction is started by simultaneously feeding a transition metal sulfate aqueous solution and a sodium hydroxide aqueous solution at a flow rate ratio of 1.8, and the total flow rate results in a residence time of 8 hours. The transition metal solution comprises Ni, Co and Mn in a molar ratio of 8:1:1, and the total transition metal concentration is 1.65mol / kg. The sodium hydroxide aqueous solution is a 25 wt % sodium hydroxide solution and a 25 wt % ammonia solution in a weight ratio of 6. The pH value is maintained at 12 by feeding a sodium hydroxide aqueous solution alone. From the beginning of all feeds, the mother liquor is continuously taken out. After 33 hours, all feed streams are stopped. By filtering the resulting suspension, washing with distilled water, drying and sieving in air at 120°C, a mixed transition metal (TM) oxyhydroxide precursor (A.1) is obtained.
[0074] The composition obtained as described above is Ni 0.8 Co 0.1 Mn 0.1 A mixed transition metal (TM) oxyhydroxide precursor was mixed with WO3 and LiOH monohydrate to obtain a W concentration of 1.0 mol% relative to Ni+Co+Mn+W and a Li / (Ni+Co+Mn+W) molar ratio of 1.03. The mixture was heated to 800°C and maintained under a forced flow of oxygen for 6 hours. The positive active material CAM.1 thus obtained was tested as described below.
[0075] In addition, CAM.1 shows excellent cycling stability at a temperature of 45 °C.
[0076] Comparative Example 1:
[0077] The mixed transition metal oxyhydroxide precursor was prepared as described in Example 1, but an aqueous sodium tungstate solution was continuously added to the stirred tank reactor, resulting in the coprecipitation of 1 mol% of tungsten relative to the sum of Ni, Co and Mn. Precursor C-(A.1) was obtained.
[0078] The precursor C-(A.1) was mixed with LiOH monohydrate at a Li / (Ni+Co+Mn+W) ratio of 1.03, and the mixture was heated in the same manner as in Example 1. A comparative positive active material C-CAM.1 was obtained. C-CAM.1 showed much lower capacity and cycle stability than CAM.1.
[0079] Embodiment 2:
[0080] The precursor (A.1) was mixed with TiO2 and LiOH monohydrate to obtain a Ti concentration of 0.3 mol% relative to Ni+Co+Mn+Ti and a Li / (Ni+Co+Mn+Ti) molar ratio of 1.03. The resulting mixture was heat treated in the same manner as in Example 1. The positive active material CAM.2 was obtained.
[0081] Moreover, CAM.2 showed excellent cycling stability at a temperature of 45 °C.
[0082] Embodiment 3:
[0083] Example 3 was carried out in the same manner as Example 2, except that Li4Ti5O was added together with LiOH monohydrate instead of TiO2. 12 , and the Ti concentration and the Li / (Ni+Co+Mn+Ti) ratio were adjusted according to Example 2. A positive electrode active material CAM.3 was obtained.
[0084] Comparative Example 2:
[0085] The mixed transition metal oxyhydroxide precursor was prepared as described in Example 1, but 0.4 mol% of Ti was added to the slurry in the form of TiOSO4 and coprecipitated at the end of the coprecipitation process. Precursor C-(A.2) was obtained.
[0086] The precursor C-(A.2) was mixed with LiOH monohydrate to obtain a Li / (TM+Ti) ratio of 1.03, and the mixture was heated in the same manner as in Example 1. A comparative positive active material C-CAM.2 was obtained. C-CAM.2 showed much lower capacity and cycle stability than CAM.2 or CAM.3.
[0087] Comparative Example 3:
[0088] The mixed transition metal oxyhydroxide precursor was prepared as described in Example 1, but 0.2 mol% of Ti was added as TiOSO4 to the slurry and coprecipitated at the end of the coprecipitation process. Precursor C-(A.3) was obtained.
[0089] The precursor C-(A.3) was mixed with LiOH monohydrate to obtain a Li / (TM+Ti) ratio of 1.03, and the mixture was heated in the same manner as in Example 1. A comparative positive active material C-CAM.3 was obtained. C-CAM.3 showed much lower first cycle capacity and cycle stability than CAM.2 or CAM.3.
[0090] Embodiment 4:
[0091] Deionized water was charged into a stirred tank reactor. The precipitation of the mixed transition metal hydroxide precursor was started by simultaneously feeding a transition metal aqueous solution and an alkaline precipitant at a flow rate ratio of 1.8, and the total flow rate resulted in a total residence time of 8 hours. The transition metal solution contained Ni, Co and Mn in a molar ratio of 8:1:1, and the total transition metal concentration was 1.65 mol / kg. The alkaline precipitant consisted of a 25 wt % sodium hydroxide solution and a 25 wt % ammonia solution in a weight ratio of 6. The pH was maintained at 12.7 by feeding a sodium hydroxide aqueous solution alone. After the particle size was stabilized, the resulting suspension was continuously taken out from the stirred vessel. A mixed transition metal (TM) oxyhydroxide precursor was obtained by filtering the resulting suspension, washing with distilled water, drying in air at 120°C and sieving.
[0092] The composition obtained as described above is Ni 0.8 Co 0.1 Mn 0.1 A mixed transition metal oxyhydroxide precursor of 6 nm was mixed with Al2O3 and LiOH monohydrate with an average particle size of 6 nm to obtain an Al concentration of 0.3 mol% and a Li / (TM+Al) molar ratio of 1.03 relative to Ni+Co+Mn+Al. The mixture was heated to 800°C and kept in a forced flow of oxygen for 6 hours. CAM.4 was obtained. The residual lithium carbonate was determined and electrochemical tests were carried out in button half cells to obtain the first cycle discharge capacity.
[0093] Comparative Example 4:
[0094] The mixed transition metal oxyhydroxide precursor was prepared as described in Example 4, but 0.3 mol % of Al was added to the reaction mixture in the form of sodium aluminate and co-precipitated. Precursor C-(A.4) was obtained.
[0095] The precursor C-(A.4) was mixed with LiOH monohydrate to obtain a Li / (TM+Al) ratio of 1.03, and the mixture was heated in the same manner as in Example 4. A comparative positive active material C-CAM.4 was obtained. C-CAM.4 showed a lower capacity than CAM.4, and in addition, the amount of residual Li species was significantly higher.
[0096] Embodiment 5:
[0097] Example 5 was carried out in the same manner as Example 4, but with the addition of Al2O3 with an average particle size of 6 nm to obtain an Al concentration of 1.0 mol% relative to Ni+Co+Mn+Al%. CAM.5 was obtained. The results are shown in Table 1.
[0098] Comparative Example 5:
[0099] Comparative Example 5 was carried out according to Comparative Example 4, but 1.0 mol % Al was added to the precursor in the form of sodium aluminate during precipitation. Precursor C-(A.5) was obtained.
[0100] The precursor C-(A.5) was mixed with LiOH monohydrate to obtain a Li / (TM+Al) ratio of 1.03, and the mixture was heated in the same manner as in Example 4. A comparative positive active material C-CAM.5 was obtained. The results are shown in Table 1.
[0101] Testing, general methods
[0102] Accordingly, electrochemical tests were carried out in button half cells, and the first cycle discharge capacities shown in Table 1 were obtained.
[0103] To prepare the positive electrode, the following ingredients were mixed with one another under stirring until a lump-free paste was obtained:
[0104] 4 g active material, 2.7 g 10 wt % polyvinylidene fluoride ("PVdF") solution in N-ethylpyrrolidone (NEP) (commercially available as Kynar HSV 900 from Arkema Group), 0.134 g of a polyvinylidene fluoride having a BET surface area of 62 m2 commercially available as "Super C65" from Imerys 2 / g of carbon black, 0.133g of graphite commercially available from Imerys as "SFG6L", 2.02g of additional NEP.
[0105] The positive electrode was prepared as follows: the paste was applied with a doctor blade onto a 20 μm thick aluminum foil until the thickness after drying was about 28 μm (about 7.5 mg active material / cm 2 ). The electrode foil is rolled to about 3g / cm 3 A coating density of . A disk-shaped positive electrode with a diameter of 20 mm was punched out of the foil. The positive electrode disk was then weighed, dried in a vacuum oven at 105 ° C for 16 hours, and introduced into an argon glove box without exposure to ambient air. A battery with a positive electrode was then constructed.
[0106] The electrochemical tests were carried out in button cells. The electrolyte used was 300 μl of a 1 M solution of LiPF6 in dimethyl carbonate / ethylene carbonate (1:1 weight ratio).
[0107] Anode: Lithium, separated from the positive electrode by a glass fiber separator.
[0108] Table 1: Properties of positive electrode materials of Examples and Comparative Examples
[0109] Added elements The first cycle discharge capacity CAM.1 1.0%W 184.5 CAM.2 0.3%Ti 195.2 CAM.3 0.3%Ti 194.0 CAM.4 0.3%Al 192.9 CAM.5 1.0%Al nd C-CAM.1 1.0%W 157.2 C-CAM.2 0.4%Ti 164.1 C-CAM.3 0.2%Ti 189.0 C-CAM.4 0.3%Al 185.3 C-CAM.5 1.0%Al nd
[0110] nd: not determined
[0111] The first cycle discharge capacity was measured at 0.1 C and 3.0-4.3 V (mA·h / g).
Claims
1. Preparation of general formula Li 1+x TM 1-x A method for producing an electrode active material for O2, wherein TM is a combination of Mn, Co and Ni in combination with at least one metal M selected from Ti and W, wherein at least 60 mol% of TM is Ni, the percentage being relative to the sum of Ni, Co and Mn, and x is 0.01-0.05, the method comprising the following steps: (a) Mix the following ingredients: (A) a mixed oxide or mixed oxyhydroxide of Mn, Co and Ni, and (B) at least one lithium compound selected from lithium hydroxide, lithium oxide and lithium carbonate, and (C) an oxide, hydroxide or oxyhydroxide of Ti or W, (b) heat treating the mixture at a temperature of 700-1000°C.
2. The method according to claim 1, wherein the mixing in step (a) is performed in a dry state.
3. The method according to claim 1, wherein step (b) is carried out in a rotary kiln or a roller hearth kiln.
4. The method according to claim 2, wherein step (b) is carried out in a rotary kiln or a roller hearth kiln.
5. The method according to any one of claims 1 to 4, wherein (A) is an oxide of Mn, Co and Ni.
6. The method of claim 5, wherein (A) is an oxide having no detectable amount of residual moisture.
7. The method according to any one of claims 1 to 4, wherein the precursor (A) is obtained by coprecipitating mixed hydroxides of nickel, cobalt and manganese, followed by drying and dehydration in air.
8. The method according to any one of claims 1 to 4, wherein the electrode active material has a molecular weight of 0.1 to 0.8 m / s as measured according to DIN-ISO 9277: 2003-05. 2 / g of BET surface area.
9. The method according to any one of claims 1 to 4, wherein in step (a), (A) the mixed oxyhydroxide of Mn, Co and Ni has a residual moisture content of 0.1-5 wt %; And wherein in step (b), the treatment is carried out under air flow and wherein the duration of step (b) is 1-24 hours.
Citation Information
Patent Citations
Method for producing lithium-mixed metal oxides and use thereof as cathode material
CN102959770A
Positive-electrode material for lithium secondary battery, secondary battery employing the same, and process for producing positive-electrode material for lithium secondary battery
CN1656633A
Nickel composite hydroxide for a lithium secondary battery, lithium composite oxide for a lithium secondary battery prepared using the nickel composite hydroxide, methods of preparing the nickel composite hydroxide and lithium composite oxide, positive electrode for a lithium secondary battery that includes the lithium composite oxide, and lithium secondary battery including the positive electrode
US20130108926A1
Cathode active material for secondary battery, preparation method therefor, and secondary battery comprising same
WO2016204563A1
Preparation method for nickel-manganese-cobalt anode material of lithium ion battery
CN102306765A